Prognostic nutritional index before surgical treatment may serve as a prognostic biomarker for patients with upper tract urothelial carcinoma: A systematic review and meta-analysis - Meng, Chunyang; Gan, Lijian; Li, Kangsen; Yi, Fulin; Peng, Lei; Li, Jinze; Li, Yunxiang (Frontiers in Nutrition, 2022)
Objective: This meta-analysis aims to assess whether the prognostic nutritional index (PNI) score before treatment can be an independent biomarker of the prognosis of patients with upper tract urothelial carcinoma (UTUC). Methods: We systematically search the Web of Science, PubMed, MEDLINE, and Cochrane Library, and the search time is up to April 2021. Use STATA 16.0 software for data processing and statistical analysis. Results: Six studies, including seven cohorts, were eventually included in our meta-analysis. The meta-analysis results showed that low PNI scores are associated with worse OS (HR:1.92; 95% CI 1.60 to 2.30; P<0.01), DFS/RFS/PFS (HR: 1.57; 95% CI 1.33 to 1.85; P<0.01), and CSS/DSS (HR: 1.79; 95% CI 1.49 to 2.16; P <0.01), which supported the PNI score as an independent prognostic biomarker for survival outcomes. The subgroup analysis and Begg’s test showed that the results were stable. Conclusions: Based on current evidence, this meta-analysis proves that the PNI score of UTUC patients before treatment is an independent prognostic biomarker. It performs well on OS, DFS/RFS/PFS, and CSS/DSS. This conclusion needs to be verified by a prospective cohort study with a larger sample size and a more rigorous design.